Development of a predictive model for severe adverse outcomes following surgery for neonatal necrotizing enterocolitis: a nomogram study based on postoperative intestinal failure beyond 42 days and death - Wu, Ying; Ren, Hongxia (Frontiers in Pediatrics, 2025)
ObjectiveTo identify the risk factors for intestinal failure occurring beyond 42 days postoperatively or death in neonates with necrotizing enterocolitis (NEC), and to develop a nomogram for predicting the likelihood of these outcomes.MethodsA retrospective cohort study was conducted on neonates who underwent surgical intervention for NEC at Shanxi Children's Hospital between January 1, 2018 and December 31, 2023. According to clinical outcomes, the patients were classified into two groups: those who either developed intestinal failure occurring beyond 42 days postoperatively or died, and a control group without intestinal failure. Univariate analysis and LASSO regression were employed to identify the optimal predictive variables. These variables were then incorporated into multivariate Logistic regression analysis to determine the risk factors for intestinal failure occurring beyond 42 days postoperatively or death. A predictive nomogram was developed based on the results. Internal validation was performed using the bootstrap resampling method. For external validation, clinical data were collected from neonates with NEC treated during two separate periods: January 2016 to December 2017 and January 2024 to January 2025, which bracketed the primary training period. The performance of the nomogram was assessed using the receiver operating characteristic (ROC) curve, calibration curve, and decision curve analysis (DCA).ResultsA total of 110 neonates with NEC were enrolled in this retrospective study. Among them, 21 developed the composite outcome of intestinal failure occurring beyond 42 days postoperatively or death. This group consisted of 5 cases of postoperative intestinal failure and 16 postoperative deaths. Among the deaths, 14 directly attributable to the progression of NEC and intestinal failure (such as enterogenic sepsis, refractory septic shock, progressive hepatic failure, etc.), one neonate died of severe respiratory infection, and one died due to the parental withdrawal of treatment. Multivariate logistic regression identified five independent risk factors significantly associated with the composite outcome: gestational age, history of asphyxia, multiple birth (twins), preoperative sepsis, and postoperative short bowel syndrome (P = 0.033, P = 0.016, P = 0.037, P = 0.015, P = 0.005). These variables were incorporated into a predictive nomogram, which demonstrated good discrimination with an area under the ROC curve (AUC) of 0.878 (95% CI: 0.804–0.952), a sensitivity of 90.5%, and a specificity of 80.9%. The external validation showed an AUC of 0.789 (95% CI: 0.632–0.947), with a sensitivity of 90% and a specificity of 66.7%, indicating good discrimination. Furthermore, both internal and external validation calibration curves showed moderate agreement between the predicted and actual outcomes, and DCA supported the model's clinical applicability.ConclusionGestational age, history of asphyxia, multiple birth, preoperative sepsis, and postoperative short bowel syndrome (SBS) were identified as key risk factors for intestinal failure occurring beyond 42 days postoperatively or death. The nomogram developed using these factors provided a quantitative, simple, and intuitive tool for clinical risk assessment of postoperative outcomes in patients with NEC.